Utilização de blog e podcasts para o ensino da genética de forma investigativa - Monte, José Pinheiro do (2024)
Teaching genetics has proven to be a challenge for some teachers due to the difficulty of establishing a strong connection between what is taught in the classroom and the student's context. An alternative to address this issue is the creation and use of technological resources. To analyze this alternative, we proposed the autonomous and investigative understanding of genetics content through the use of blogs and podcasts for 11th-grade high school students. The nature of the research employed here was action research, using the scientific method for both qualitative and quantitative approaches, with data collection conducted from August 1st to October 13th, 2023, involving 117 students from a full-time school in Pernambuco. To better analyze the data obtained, we administered a pre-test questionnaire to diagnose the students' prior knowledge and a post-test questionnaire for result comparison. The results demonstrated that investigative processes for constructing blogs and podcasts, as well as the investigative workshops conducted, are alternatives to be adopted in the classroom to improve understanding of genetics concepts. The application of pre and post-test questionnaires was essential for identifying the impact of the adopted methodology on student learning. In the post-test, the methodology's impact was also perceived through comments and positive acceptance of the activities, as well as word-of- mouth dissemination to other students in the school. As a product of this research, a user manual was produced with the planned and developed lessons, described as sequentially organized lesson plans to facilitate implementation.